Efficacy of single-dose compared with split-dose low-volume polyethylene glycol for colonoscopy preparation: a randomized controlled trial - Islam, Nafizul; Alam, Shahinul; Islam, Mahjabin; Rahman, M. Masood-Ur; Mohiuddin, Syed Arafat; Dhali, M. Shahin; Khan, M. Morshedul Alam; Alam, M. Razibul (International Journal of Research in Medical Sciences, 2026)
Background: A successful colonoscopy requires adequate bowel preparation. Polyethylene glycol (PEG) is an appropriate bowel preparation agent for colonoscopy. The timing of ingestion of PEG solution is a major determinant of the quality of bowel preparation which has evolved from the previous day evening to the currently recommended split-dose regimen in the West. It was observed that consuming an entire or a portion of PEG on the previous day can interfere with routine activities, work and sleep. Objectives were to compare the efficacy of single‑dose morning low-volume PEG with split‑dose low-volume PEG as bowel cleansing preparation for colonoscopy in a tertiary care hospital. Methods: Based on the bowel preparation agent they received-a single-dose (Group-A) or a split-dose (Group-B) of a 2 L PEG solution-128 participants were randomly assigned to one of two groups. All colonoscopy was performed between 10 AM and 12 PM without sedation. The Boston bowel preparation scale (BBPS) was used to evaluate the quality of bowel preparation. Results: The single-dose group had a better quality of bowel preparation than the split-dose group with a total BBPS score of 7.09±1.18 versus 6.61±1.20 (p=0.023). Similarly, higher proportion of patients in single-dose group (87.5%) achieved adequate bowel preparation (BBPS score ≥6) when compared to those in split-dose group (78.1%) (p=0.160). Conclusions: Single-dose morning low-volume PEG provided an improved bowel preparation than the split-dose regimen for morning colonoscopy in the Bangladeshi population.